Hype: The Capitalist Degree of Induced Participation - Yuri Di Liberto (Review of Capital as Power, 2022)
* Winner of the 2022 RECASP Second Essay Prize * Power is usually considered as either a `positive' or `negative' construct, as in the power to force action versus the power to forbid it. This paper explores a hybridized approach to power based on the idea of `induced participation'. Building on Bichler and Nitzan's theory of `capital as power', I argue that capitalism reinforces its hold on society through the strategic use of `hype'. The idea is that capitalists counteract resistance by boosting confidence in the promise of reward, a process that can be better understood using the concept of hype.
Keywords: P16; P26; G; Z1; 330; capital as power; chreods; epochal changes; finance; hype; reward; social paradigm